2010
DOI: 10.1111/j.1420-9101.2010.02193.x
|View full text |Cite
|
Sign up to set email alerts
|

Selection for increased body length in Subantarctic fur seals on Amsterdam Island

Abstract: The traditional distinction between ecological and evolutionary times is eroding, calling for tighter links between ecology and evolution. An example of such a brigde between the two disciplines is the so‐called ‘animal model’, a methodology initially developed by animal breeders, which has become very popular among ecologists studying contemporary microevolution. Using a Bayesian multi‐trait ‘animal model’, we investigated the quantitative genetics of body size, a fitness‐related trait, in Subantarctic fur se… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 57 publications
(114 reference statements)
0
12
0
Order By: Relevance
“…As this population has reached its carrying capacity, the intraspecific competition level should accordingly be higher in the Amsterdam population than at Crozet (Gilpin & Ayala ). In addition, Authier, Cam & Guinet () have reported that the probability of breeding success has decreased in Amsterdam as the population has stabilized, most probably as a consequence of increasing competition. Therefore, the impact of interspecific competition in the subantarctic fur seal (sympatry in Crozet, allopatry in Amsterdam) may be masked by effects of contrasted level of intraspecific competition between the two populations and has not been investigated in this species.…”
Section: Discussionmentioning
confidence: 99%
“…As this population has reached its carrying capacity, the intraspecific competition level should accordingly be higher in the Amsterdam population than at Crozet (Gilpin & Ayala ). In addition, Authier, Cam & Guinet () have reported that the probability of breeding success has decreased in Amsterdam as the population has stabilized, most probably as a consequence of increasing competition. Therefore, the impact of interspecific competition in the subantarctic fur seal (sympatry in Crozet, allopatry in Amsterdam) may be masked by effects of contrasted level of intraspecific competition between the two populations and has not been investigated in this species.…”
Section: Discussionmentioning
confidence: 99%
“…A question currently receiving growing attention is the extent to which morphological (e.g., structural size), physiological (e.g., body condition) and personality traits are determined genetically and are heritable (e.g., Authier et al 2011;Dingemanse et al 2004;Dingemanse and Réale 2005;Drent et al 2003;Garnett 1981;Kontiainen et al 2007;Larsson and Forslund 1992;Larsson 1993;Merilä et al 2001;Réale and Festa-Bianchet 2003;Schlutter and Gustafsson 1993;Stamps and Groothuis 2010;Téplitsky et al 2008;van Noordwijk et al 1988;van Oers et al 2005). Similarly, fitness components themselves may be heritable (e.g., Charmantier et al 2006a, b;Kontiainen et al 2007).…”
Section: Heritability and Parental Effectsmentioning
confidence: 99%
“…The parameters σϕ2 and σnormalrepro2 are variance parameters, and normalcor is a correlation parameter bounded between −1 and 1. The multivariate normal distribution was used for convenience as often in empirical investigations (e.g., Authier, Cam, & Guinet, ; Browne, McCleery, Sheldon, & Pettifor, ; Cam et al., ).…”
Section: Notationsmentioning
confidence: 99%